2020
DOI: 10.1016/j.ijid.2019.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in interferon pathway genes and risk of Mycobacterium tuberculosis infection in contacts of tuberculosis cases in Brazil

Abstract: Background: Host genetic polymorphisms may be important in determining susceptibility to Mycobacterium tuberculosis (Mtb) infection, but their role is not fully understood. Detection of microbial DNA and activation of type I interferon (IFN) pathways regulate macrophage responses to Mtb infection. Methods: We examined whether seven candidate gene SNPs were associated with tuberculin skin test (TST) positivity in close contacts of microbiologically confirmed pulmonary TB patients in Brazil. Independent associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Previous studies have found associations of NLRP3 and TLR2 polymorphisms with susceptibility to TB 5,[15][16][17]19,21 . In our study of the Taiwanese population, we found that the TC genotype of NLRP3 rs34298354 was associated with decreased risk of TB.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have found associations of NLRP3 and TLR2 polymorphisms with susceptibility to TB 5,[15][16][17]19,21 . In our study of the Taiwanese population, we found that the TC genotype of NLRP3 rs34298354 was associated with decreased risk of TB.…”
Section: Discussionmentioning
confidence: 94%
“…AIM2-deficient mice show high susceptibility to Mtb due to impaired production of IL-18 and IFN-γ and reduced activation of caspase-1 14 . In recent years, associations of inflammasome gene polymorphisms with susceptibility to TB and the development of TB have been reported 4,15,16 . NLRP3 polymorphism rs35829419 has been associated with extrapulmonary TB in Ethiopia 15 , and IFI16 polymorphisms rs1101998 and rs1633256 have been associated with tuberculin skin test positivity in contacts of TB patients in Brazil 16 .…”
mentioning
confidence: 99%
“…The method was found to have poor specificity and accuracy due to the cross-reactivity with antigens present in other mycobacterial species, including the M. bovis Bacillus Calmette–Guerin (BCG) vaccine strain. Moreover, there is accumulating evidence that human genetics play an important role in the development of DTH to PPD [ 2 , 3 , 4 ]. Interferon-γ release assays, which measure the release of IFN-γ in whole blood samples following in vitro stimulation with M.tb -specific antigens, i.e., early secreted antigenic target-6 (ESAT-6), culture filtrate protein 10 (CFP-10), and TB7.7, are recommended as an alternative to the TST.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of these diseases and the establishment of local transmission in traditionally non-endemic areas, due to migration and travel, have been revealed over the last years. Diseases such as Chikungunya (11-16), Zika (17-24), Yellow Fever (25-28), Dengue (29)(30)(31)(32)(33), Oropouche, Madre de Dios virus, Iquitos virus (34,35), Mayaro Fever (36,37), Ebola (38)(39)(40)(41)(42), Nipah virus, arenaviruses such as Lassa (43), Machupo (44,45), Chapare (45,46), Junin (47), zoonotic Malaria (48), Severe Fever with Thrombocytopenia Syndrome (49), Plague (50), Crimean-Congo Hemorrhagic Fever, Acute Orally Transmitted Chagas Disease (51)(52)(53)(54), Visceral and Diffuse Cutaneous Leishmaniasis (55,56), Toxoplasmosis (57)(58)(59), Tick-Borne Diseases (60,61), Rift Valley Fever, Tuberculosis (62), Leprosy (63)(64)(65)(66)(67), Avian Influenza (68)(69)(70), Orthohantavirus (71)(72)…”
mentioning
confidence: 99%
“…The impact of these diseases and the establishment of local transmission in traditionally non-endemic areas, due to migration and travel, have been revealed over the last years. Diseases such as Chikungunya ( 11 16 ), Zika ( 17 24 ), Yellow Fever ( 25 28 ), Dengue ( 29 33 ), Oropouche, Madre de Dios virus, Iquitos virus ( 34 , 35 ), Mayaro Fever ( 36 , 37 ), Ebola ( 38 42 ), Nipah virus, arenaviruses such as Lassa ( 43 ), Machupo ( 44 , 45 ), Chapare ( 45 , 46 ), Junin ( 47 ), zoonotic Malaria ( 48 ), Severe Fever with Thrombocytopenia Syndrome ( 49 ), Plague ( 50 ), Crimean-Congo Hemorrhagic Fever, Acute Orally Transmitted Chagas Disease ( 51 54 ), Visceral and Diffuse Cutaneous Leishmaniasis ( 55 , 56 ), Toxoplasmosis ( 57 59 ), Tick-Borne Diseases ( 60 , 61 ), Rift Valley Fever, Tuberculosis ( 62 ), Leprosy ( 63 67 ), Avian Influenza ( 68 – 70 ), Orthohantavirus ( 71 – 75 ), and Toxocariasis ( 76 , 77 ) have posed a significant impact to human health. Furthermore, zoonotic epidemics and pandemic coronaviruses, such as the Severe Acute Respiratory Syndrome (SARS), the Middle East Respiratory Syndrome (MERS) ( 78 82 ), and the ongoing SARS-CoV-2/COVID-19 ( 83 , 84 ) pandemic, have caused a profound economical and social disruption threatening to overwhelm public health systems globally ( 85 ) ( Table 1 ).…”
mentioning
confidence: 99%